The association between genetically determined ABO blood types and major depressive disorder - Garvert, Linda; Baune, Bernhard T; Berger, Klaus; Boomsma, Dorret I; Breen, Gerome; Greinacher, Andreas; Hamilton, Steven P; Levinson, Douglas F; Lewis, Cathryn M.; Lucae, Susanne; Magnusson, Patrik K E; Martin, Nicholas G; et al. (Psychiatry research, 2021)
ABO blood types and their corresponding antigens have long been assumed to be related to different human diseases. So far, smaller studies on the relationship between mental disorders and blood types yielded contradicting results. In this study we analyzed the association between ABO blood types and lifetime major depressive disorder (MDD). We performed a pooled analysis with data from 26 cohorts that are part of the MDD working group of the Psychiatric Genomics Consortium (PGC). The dataset included 37,208 individuals of largely European ancestry of which 41.6% were diagnosed with lifetime MDD. ABO blood types were identified using three single nucleotide polymorphisms in the ABO gene: rs505922, rs8176746 and rs8176747. Regression analyses were performed to assess associations between the individual ABO blood types and MDD diagnosis as well as putative interaction effects with sex. The models were adjusted for sex, cohort and the first ten genetic principal components. The percentage of blood type A was slightly lower in cases than controls while blood type O was more prominent in cases. However, these differences were not statistically significant. Our analyses found no evidence of an association between ABO blood types and major depressive disorder.
Gesehen am 14.10.2021